Cultural adaptation of patient-reported indicator surveys (PaRIS) patient and primary care practice questionnaires to the slovenian context - Ambrož, Matija (Zdravstveno varstvo, 2025)
Introduction: The objective of the study is to describe the adaptation process (with emphasis on cognitive testing) of the Slovenian version of the PaRIS international survey, including two questionnaires to assess patient-reported health outcomes and the experiences of adults living with one or more chronic conditions managed in primary care settings: (1) Patient questionnaire (targets patients aged 45 and older) and (2) Provider questionnaire (targets health care providers working in primary care). Methods: The translation process of both PaRIS questionnaires followed a team-based double translation and reconciliation approach. Cognitive interviewing with 29 participants was performed. An analysis grid and debriefing were implemented, and the cognitive testing rating was assessed for each tested question. Cross-national error source typology (CNEST) was used. Results: The results of cognitive interviewing revealed difficulties in 30 questions / segments (out of a total of 44 tested) in the Patient questionnaire and difficulties in 23 questions / segments (out of a total of 24 tested) in the Provider questionnaire. In both questionnaires most difficulties were identified as poor source question design. Conclusions: Our study showed that cognitive interviewing is a crucial step in questionnaire adaptation, especially while transferring internationally developed questionnaires on Patient Reported Experience Measures and Patient Reported Outcome Measures into different national contexts. Through a rigorous process of translation and cognitive testing, we obtained better quality PREMs and PROMs measures in the Slovenian language. However, the measurement tools need to be piloted, and psychometrically evaluated in future to test reliability and validity.
Keywords: cognitive testing; izidi zdravstvene oskrbe; kognitivno testiranje; osnovno zdravstvo; outcome measure; patient reported; primary care